Cholera outbreak and associated risk factors in Dollo Ado district, Ethiopia: un-matched case-control study, 2023 - Hagos, Fitsum; Ayele, Habtamu Molla; Kebede, Eyob Hailu; Abagero, Abdulnasir; Kifle, Awgichew (Frontiers in Epidemiology, 2025)
BackgroundCholera is a highly contagious bacterial disease that causes severe watery diarrhea. It spreads mainly through contaminated food or water containing Vibrio cholerae O139 and remains a major global public health threat. We investigated an outbreak to identify its cause, source, and risk factors and to develop control measures.MethodA suspected case was classified as the occurrence of acute watery diarrhea in a Dollo Ado District resident aged 2 or older between February 2, 2023 and March 15, 2023. A confirmed case was a suspected case with Vibrio cholerae detected in the patient's stool sample. An investigation of the outbreak was conducted; cases were described and the environment, where contamination may take place assessed and an unmatched case-control study conducted in Suftu Kebele, which served as the epi center of the outbreak. Logistic regression was used to identify risk factors for cholera infection.ResultsA total of 92 cases were identified, including 66 males and 26 females, with four deaths (4.3% fatality rate). Males had a higher attack rate (2.4 per 1,000 people) than females (1.6 per 1,000 people). Suftu village was the hardest-hit area (attack rate: 41 per 1,000 people). The outbreak began after a person suspected of having cholera returned from mandera, kenya, on February 2, 2023. Five days later, cases emerged in suftu village. Many residents practiced open defecation and used the dawa river for bathing, washing clothes, and drinking. Using untreated river water significantly increased the risk of infection (AOR = 20, 95% CI: 5.2–73).ConclusionThe outbreak likely started at a funeral of a suspected cholera case, spreading through contaminated river water. It was contained within a week by restricting river water use and preventing further contamination.